Emotional Literacy and Students' Academic Achievement in Elementary Schools - Emma Rumahlewang; Edy Janter Latumahina; John Rafafy Batlolona (Unram Journal of Community Service, 2025)
This community service activity aims to improve the emotional literacy of elementary school students in Southeast Maluku and Tual City as an effort to support academic achievement and positive character development. Emotional literacy is considered important because it helps students recognize, understand, and manage emotions, thereby improving concentration, learning motivation, and social interaction in the school environment. The activity was implemented using a participatory approach through interactive lectures, group discussions, simulations (role plays), and joint reflections involving students in grades IV–VI. Evaluation was carried out qualitatively through observation and teacher feedback. The results of the activity showed an increase in students' abilities to identify emotions, control behavior, and participate more actively in the learning process. Social-emotional support from teachers, including communication with parents and facilitating educational assistance for underprivileged students, contributed to increased attendance and learning motivation. Overall, strengthening emotional literacy has been shown to contribute to learning engagement and improvements in students' academic attitudes. This activity confirms that integrating emotional literacy into elementary education is an effective strategy for improving the quality of learning and building student character sustainably.